Faktor-Faktor Kritis Keberhasilan Implementasi Enterprise Resource Planning (ERP): Sebuah Tinjauan Literatur - Pandena Kicky Basuki Putri; Muhammad Aziz Muallif (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Enterprise Resource Planning (ERP) is an integrated information system that connects various business functions within a single centralized database, making it the operational backbone of modern organizations, from large enterprises to small and medium enterprises (SMEs). Although its benefits are widely recognized, ERP implementation failure rates remain reportedly high, with some studies citing failure rates exceeding 70 percent of all projects undertaken. This article presents a narrative literature review of the critical success factors (CSFs) of ERP implementation based on prior systematic reviews and empirical studies. The review identifies six main groups of factors that consistently appear in the literature: top management support, change management, user training and education, user involvement, data quality and validation, and system-process fit. This article also discusses the differing implementation challenges faced by large organizations compared to SMEs, given that resource constraints in SMEs create a distinct risk profile. This review is intended as a preliminary reference for researchers and practitioners in designing more targeted ERP implementation strategies and to open avenues for further empirical research in the Indonesian organizational context.